CBCT-based online adaptive radiotherapy of the bladder – geometrical and dosimetrical considerations compared to conventional IGRT - Jann Fischer; Laura Anna Fischer; Jona Bensberg; Natalia Bojko; Mohamed Bouabdallaoui; Jasper Frohn; Petra Hüttenrauch; Mandy Klingebiel; Daniela Schmitt; Katharina Tegeler; Daniela Wagner; Alina Wenzel; et al. (Radiation Oncology)
Abstract Background Bladder cancer radiotherapy presents unique challenges due to the dynamic anatomy of the bladder and the surrounding organs. Conventional image-guided radiotherapy (IGRT) relies on fixed treatment margins and daily couch corrections, which can result in suboptimal dose delivery. Cone Beam Computed Tomography (CBCT)-based online adaptive radiotherapy (oART) allows daily re-optimization of treatment plans, potentially improving target dose coverage while minimizing exposure to organs at risk (OAR). This study compares oART with IGRT in bladder cancer patients. Methods 160 oART fractions delivered using the Ethos system (Varian Medical Systems, Palo Alto, CA, USA) were analyzed and compared to conventional IGRT. For each adaptive fraction (fx), three plans were evaluated: the scheduled plan (initial plan recalculated based on daily CBCT), the adapted plan (re-optimized to daily anatomy), and the verification plan (dose distribution recalculated on the verification CBCT - vCBCT). Geometric variations, dose-volume parameters and treatment times were analyzed. Clinical plan acceptability was assessed using predefined dose-volume parameters. Dose coverage on the target’s surface was analyzed using a novel method and visualized via Mercator projections. Results Despite drinking guidelines, bladder volumes varied significantly day-to-day. Dose coverage of the clinical target volume (CTV) improved significantly with adaptation (median D98% 88.4–97.8%, p < 0.01) and further after vCBCT (median D98% 98.1%, p < 0.01), with a reduced interquartile range (IQR). Planning target volume (PTV) D98% also improved with adaptation (median 69.5–92.8%, p < 0.01) and after vCBCT (median 91.8%, p < 0.01), with decreasing IQR. OAR doses showed reduced variability and a measurable dosimetrical benefit. Spatial dose distribution on the surface of the targets improved for adaptation. Plan acceptability in retrospect almost doubled from 11.9% for scheduled plans to 23.1% for adapted plans and 22.5% for verification plans. The scheduled plans were never chosen for treatment. Median oART treatment time was 14 min, compared to 9 min for IGRT. Conclusions Treatment times were approximately 1.5 times longer than IGRT; however, CBCT-based oART enhanced target dose coverage, reduced OAR doses, and decreased variability in both target and OAR doses compared to IGRT, while also improving plan acceptability, although the results should be interpreted with caution due to the limited sample size and single-center design. Trial registration Not applicable.